2014
DOI: 10.1108/nfs-03-2013-0036
|View full text |Cite
|
Sign up to set email alerts
|

Visual information influences consumer fast-food choices

Abstract: Purpose – The purpose of this paper is to investigate the influence of visual information cues such as a heart icon vs the calories and fat content on the selection of healthy food in fast-food restaurants (FFRs). Design/methodology/approach – An online survey design providing a fast-food menu was implemented to collect responses from the participants. The survey respondents were recruited from a large South-western university in the USA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…After eliminating duplicates, 21,239 studies were included in the title reading stage and 436 studies were retained for abstract evaluation. Fifty-six full-text publications were included in the full-text review and 42 were excluded [ 36 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. Five studies [ 51 , 97 , 98 , 99 , 100 ] classified as “A” and nine [ 50 , 101 , 102 , ...…”
Section: Resultsmentioning
confidence: 99%
“…After eliminating duplicates, 21,239 studies were included in the title reading stage and 436 studies were retained for abstract evaluation. Fifty-six full-text publications were included in the full-text review and 42 were excluded [ 36 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ]. Five studies [ 51 , 97 , 98 , 99 , 100 ] classified as “A” and nine [ 50 , 101 , 102 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Studies that include mostly young adult participants have found mixed results with the implementation of different menu labelling formats (43)(44)(45)(46)(47)(48)(49) . In the present study, one-third of the sample did not notice the symbols, and only 30 % of those who noticed them (20 % of the total sample) reported being influenced by them, and this was dependent on the purchase factors that consumers considered most important such as taste and price, and what they considered as barriers to purchasing healthy foods.…”
Section: Discussionmentioning
confidence: 99%